Uma avaliação do capital social dos alunos da Universidade do Oeste de Santa Catarina (UNOESC) - Alyne Sehnem; Janaina Macke; Adriana Locatelli Bertolini (Ciências Sociais Unisinos)
The concept of social capital related to the economic development of regions and countries began to achieve significance in the 1990s. Nevertheless, the measurement of social capital still faces some difficulties, because it requires a combination of statistical measures to find results that are reliable for the reality of the given community. The present study aims to measure the social capital level of undergraduate students in three cities of the Far West of Santa Catarina (south of Brazil), viz. Maravilha, São José do Cedro e São Miguel do Oeste. The survey relies on previous works by Macke (2006), Macke et al. (2010) and the evaluation model proposed by Onyx and Bullen (2000). Descriptive statistics, factorial analysis, linear regression and analysis of variance have been used, trough the software SPSS (Statistical Package for the Social Science). The results point out the variables related to "Participation in the community" as having the lowest levels of social capital, whereas the variables related to "Feelings of safety" and "Work connections" reach the best performance. The analysis of the results considers the sociocultural aspects of the region and aims to find elements related to the characteristics and the endogenous forces of the community.